SINERGI LANUD ISKANDAR DAN DITPOLAIRUD PADA MOBILITAS UDARA DALAM MENDUKUNG OPERASI SAR DI WILAYAH PROVINSI KALIMANTAN TENGAH - Kukuh Priyo Taruno,; Ari Ganjar Herdiansah,; Handoko Ivan (Strategi Pertahanan Udara, 2022)
This study describes the Synergy of Iskandar and Ditpolairud Air Base on Air Mobility in Support of SAR Operations in the Province of Central Kalimantan. The method used in this study is a qualitative method, researchers have collected and processed data with a qualitative descriptive approach. Based on the results of the analysis, this study concludes, among other things, that the cooperation between the two has not met pre-disaster indicators which include prevention, mitigation, preparedness, and early warning activities. in the context of prevention. The cooperation of the two has an important role at the stage of a disaster, both of them have contributed in providing air mobility operation assistance, in this phase the role of the two institutions has its own urgency compared to other elements that do not have the capability of air mobility operations. In cooperation, the two do not have the capacity in the recovery process, because the ability of air mobility is used during evacuation, namely at the stage of a disaster. The collaboration between Iskandar Airbase and the Ditpolairud Polda in SAR operations in the Central Kalimantan Province plays a major role in activities during disaster which includes emergency response activities to relieve temporary suffering, such as search and rescue (SAR), emergency assistance and evacuation.